(untitled) (Journal of the Bangladesh Agricultural University, 2010)
An experiment was carried out with Barbodes gonionotus for 4 months (120 days) in the experimental ponds of size of 2.8 decimal each with the same stocking densities of 57 fish/dec. in all the treatments. Each pond was divided into two equal halves by synthetic net fixed with bamboo. Three treatments (T1, T2 and T3) each with two replicates were used. The fish were reared in only fertilized pond (T1), in fertilized and rice bran fed pond (T2) and only rice bran fed pond (T3). During the study period the water quality parameters such as temperature, transparency, water depth, dissolved oxygen, pH and plankton biomass in all treatments were within productive range. The observed growth parameters such as mean weight gain were 36.24 g, 65.85 g and 44.41 g, percent weight gain were 120.80%, 219.52% and 148.03%, the average daily gain were 1.28 g, 2.37 g and 1.64 g, the specific growth rate were 0.66%, 0.97% and 0.77%, in T1, T2 and T3 respectively. The gross total productions of Sharpunti were 844.64, 1292.85 and 930.36 kg/ha/120 days. The net productions were 462.49, 888.39 and 555.35 kg/ha/120 days in T1, T2 and T3 respectively. The gross and net total productions in T2 were highest compared to T1 and T3. Sharpunti showed highest growth performance in T2 when fine rice bran was used as feed and simultaneously the pond was fertilized. Keywords: Rice bran; Growth; Survival; Thai sharpunti DOI: 10.3329/jbau.v8i1.6414 J. Bangladesh Agril. Univ. 8(1): 161-171, 2010